2022
DOI: 10.1111/tan.14704
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of antibodies to HLA according to different cut‐off values of mean fluorescence intensity in haploidentical allograft candidates: A prospective study of 3805 subjects

Abstract: The importance of anti‐HLA antibodies in transplantation settings, such as HLA‐mismatched or haploidentical hematopoietic stem cell transplantation and platelet refractoriness, is widely recognized. In previous reports, it was mentioned that several cut‐off values of donor‐specific anti‐HLA antibodies mean fluorescence intensity (MFI) were related to graft rejection in the environment of HLA mismatched stem cell transplantation and the aim of this study was to investigate the prevalence and risk factors of ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Transfusions with related-donor platelets have better haemostasis and a lower likelihood of bleedingespecially if the three HLA-A, -B, and -C loci are identical. 3 Factors other than eplet-or antigen mismatch also have a role in immunization after platelet transfusion. Indeed, the results of a recent study in a mouse model showed that chemotherapy led to enhanced alloantibody responses to allogeneic platelet transfusion.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Transfusions with related-donor platelets have better haemostasis and a lower likelihood of bleedingespecially if the three HLA-A, -B, and -C loci are identical. 3 Factors other than eplet-or antigen mismatch also have a role in immunization after platelet transfusion. Indeed, the results of a recent study in a mouse model showed that chemotherapy led to enhanced alloantibody responses to allogeneic platelet transfusion.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 In a cohort of 3805 patients with haematologic disease, the prevalence of class I or II anti-HLA antibodies ranged from 4.6% to 20.2% (depending on the cut-off value for positivity used). 3 HLA antibodies can be formed through the activation of HLA-specific humoral immune mechanisms, in several ways; the main settings include pregnancy, blood transfusion (especially platelet transfusion), and previous organ transplantation. In patients with haematologic disease, the presence of anti-HLA DSAs (defined according to various mean fluorescence intensity (MFI) cut-off values, ranging from 1000 to 10,000) was associated with platelet transfusion and pregnancy.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations